Penempatan dan Lingkungan Kerja Non Fisik Terhadap Kinerja Melalui Semangat Kerja Pegawai pada Kantor Wilayah Badan Pertanahan Nasional Provinsi Kalimantan Timur - Afni Dwi Astuti; Dirga Lestari (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to analyse the influence of staff placement and the non-physical work environment on staff performance, with work motivation serving as a mediating variable, at the Regional Office of the National Land Agency in East Kalimantan Province. Furthermore, this study also aims to identify the extent to which the alignment of staff placement with their competencies and educational background can enhance work motivation and contribute to optimal performance. This study employs a quantitative approach using a survey method, involving the distribution of questionnaires to 120 respondents who are Civil Servants who have undergone a transfer and have more than two years' service. Data analysis utilises Structural Equation Modelling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS. The results indicate that placement and the non-physical work environment have a positive and significant effect on work motivation. Placement also has a positive and significant effect on employee performance, whilst the non-physical work environment does not have a direct significant effect on performance. Work motivation was found to have a positive and significant influence on performance and was the most dominant variable in the research model. Furthermore, work motivation was found to partially mediate the influence of placement on performance and fully mediate the influence of the non-physical work environment on performance.